Full-biomass porous photo-thermal composite material with synergistic surface microstructure as well as preparation method and application of full-biomass porous photo-thermal composite material
By preparing fully biomass porous photothermal composite materials with surface microstructure efficiency, using its multi-stage porous structure and carbon particles, the problems of high cost and low efficiency of existing photothermal interface evaporation materials are solved, and efficient, low-cost, green seawater desalination materials are achieved, with good water absorption and rapid evaporation and purification capabilities.
Patent Information
- Application Number
- CN202411577347.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-18
AI Technical Summary
The existing photothermal interface evaporation materials have high manufacturing costs, low efficiency, heavy pollution in the manufacturing process, and easy to cause secondary pollution in water bodies, and it is difficult to meet the demand for efficient, low-cost, green and degradable materials of seawater desalination technology.
Using a fully biomass porous photothermal composite material with surface microstructure efficiency, a composite material with multi-stage porous structure and carbon particles is prepared by mixing wood powder, bio-based polymer materials and biomelanin, heating treatment, drying, molding treatment and low-temperature carbonization treatment, and the photothermal conversion efficiency is improved by using its surface microstructure and pore structure.
It has achieved green and low-cost production of high-performance photothermal fully biomass porous composite materials with good water absorption, high photothermal conversion capabilities, rapid evaporation and purification capabilities, and degradable high-performance photothermal fully biomass porous composite materials, solving the high cost and low efficiency of traditional materials and reducing the risk of water pollution.
Smart Images

Figure HDA0005122119430000011 
Figure HDA0005122119430000012 
Figure HDA0005122119430000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials and processing thereof, and specifically relates to a full-biomass porous photothermal composite material with enhanced surface microstructure, and a preparation method and application thereof. Background Art
[0002] The rapid development of society has brought about serious water pollution and climate change, which has led to an increasing demand for water resources, while freshwater resources are very limited. As an important measure to solve the problem of water shortage and ensure water safety, seawater desalination technology has become a major frontier and hot spot for research at home and abroad. Therefore, the seawater desalination industry has great potential, and it can be foreseen that the seawater desalination industry will develop rapidly in the near future.
[0003] At present, the main technologies for seawater desalination include reverse osmosis, distillation, multi-stage flash evaporation, electrodialysis, etc. However, these traditional seawater desalination technologies generally have technical defects such as the large-scale use of chemical reagents, low yield, and high cost, which cause serious pollution to the ocean and greatly limit the further development and application of seawater desalination technology. Solar-driven photothermal interface desalination and purification technology uses photothermal conversion to achieve interfacial heating of water bodies and realizes the desalination process dominated by green energy. It is the mainstream development direction of current seawater desalination technology. However, as an important part of solar interface evaporation technology, photothermal interface evaporation materials currently have problems such as high manufacturing cost, low efficiency, heavy pollution in the manufacturing process, and easy to cause secondary pollution of water bodies. Therefore, how to directly use biological resources to develop more efficient, low-cost, green, and degradable photothermal interface desalination materials has become an important way to solve the bottleneck problems currently faced by photothermal interface evaporation materials. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a method for preparing a full-biomass porous photothermal composite material with enhanced surface microstructure.
[0005] The present invention also provides an all-biomass porous photothermal composite material with enhanced surface microstructure prepared by the above method.
[0006] The present invention also proposes the application of the above-mentioned all-biomass porous photothermal composite material with enhanced surface microstructure.
[0007] According to one aspect of the present invention, a method for preparing a surface microstructure-enhanced all-biomass porous photothermal composite material is proposed, the preparation method comprising the following steps:
[0008] S1, mixing wood powder, bio-based polymer material and biomelanin to obtain a mixture;
[0009] S2, heating the mixture to obtain a gelatinized blend;
[0010] S3, drying the gelatinized blend, and then performing a molding process at 100° C.-190° C. to obtain a carbonized precursor;
[0011] S4, placing the carbonized precursor in a mold and sealing it, and performing a carbonization treatment to obtain the all-biomass porous photothermal composite material.
[0012] In some embodiments of the present invention, the wood powder comes from nature, including but not limited to agricultural and forestry resources such as straw, branches, bamboo, and agricultural and forestry wastes such as dead wood leaves.
[0013] In some embodiments of the present invention, the wood powder includes but is not limited to one of straw, pine wood and bamboo.
[0014] In some embodiments of the present invention, the wood powder is pine wood powder.
[0015] In some embodiments of the present invention, the wood powder has a sieve mesh number of 48 to 300 meshes, is a powder made from commonly used wood, is coated with starch, and then is carbonized to form holes, and the particle size of the wood powder is related to the pore size of the continuous holes.
[0016] In some embodiments of the present invention, the bio-based polymer material includes but is not limited to one of starch and cellulose.
[0017] In some embodiments of the present invention, the biomelanin comprises at least one of cuttlefish ink and squid ink.
[0018] In some embodiments of the present invention, the added mass ratio of the wood powder, the bio-based polymer material and the biomelanin is (3-6): (3-6):1.
[0019] In some embodiments of the present invention, the added mass ratio of the wood powder, the bio-based polymer material and the biomelanin is (4-5): (4-5):1.
[0020] In some embodiments of the present invention, the mixture further comprises water.
[0021] In some embodiments of the present invention, the mixing is performed by a mixing machine. The materials are fully stirred and premixed by high-speed mechanical premixing to ensure that the wood powder is dispersed into the starch matrix and that the cuttlefish powder can fully penetrate into the surface of the polymer material and the gaps between the particles, so that the composite material exhibits disorder inside.
[0022] In some embodiments of the present invention, the rotation speed of the mixing machine is 200-400 r / min.
[0023] In some embodiments of the present invention, the rotation speed of the mixing machine is about 300 r / min.
[0024] In some embodiments of the present invention, the mixing time is 10-20 minutes.
[0025] In some embodiments of the present invention, the mixing time is 13-17 minutes.
[0026] In some embodiments of the present invention, the mixing time is 15 minutes.
[0027] In some embodiments of the present invention, the heating method adopts water bath heating.
[0028] In some embodiments of the present invention, the heating temperature is 60-95°C.
[0029] In some embodiments of the present invention, the heating temperature is 85-92°C.
[0030] In some embodiments of the present invention, the heating time is 10-25 min.
[0031] In some embodiments of the present invention, the heating time is 12-18 minutes.
[0032] In some embodiments of the present invention, the drying is carried out by oven drying.
[0033] In some embodiments of the present invention, the drying is vacuum drying.
[0034] In some embodiments of the present invention, the drying temperature is 75-85°C.
[0035] In some embodiments of the present invention, the drying temperature is 80°C.
[0036] In some embodiments of the present invention, the drying time is 1-3 hours.
[0037] In some embodiments of the present invention, the drying time is 1.5-2.5 hours.
[0038] In some embodiments of the present invention, the drying time is 2 hours.
[0039] In some embodiments of the present invention, the gelatinized blend has a water content of 2 to 10 wt % after drying.
[0040] In some embodiments of the present invention, the water content of the gelatinized blend after drying is 6 wt %.
[0041] In some embodiments of the present invention, the molding time is 5-15 minutes.
[0042] In some embodiments of the present invention, the molding time is 8-15 minutes.
[0043] In some embodiments of the present invention, the molding pressure is 5-15 MPa.
[0044] In some embodiments of the present invention, the molding pressure is 8-12 MPa.
[0045] In some embodiments of the present invention, the mold is a mold comprising a template having a surface microstructure.
[0046] In some embodiments of the present invention, the surface microstructure is a papillary microstructure with a light trapping effect, and may also be an inverted pyramid, column, claw, or other microstructure with a light trapping effect.
[0047] In some embodiments of the present invention, the mold is a non-overflow compression mold, the inner cavity size of the mold is slightly larger than the sample size, and the top of the mold is a mold cavity with a surface microstructure.
[0048] In some embodiments of the present invention, after the sealing, the air content in the sealed mold is 5% to 10%. The carbonized precursor is placed in the sealed mold but does not fill the sealed mold completely, leaving a certain gap, that is, the air content.
[0049] In some embodiments of the present invention, the carbonization process is performed in a muffle furnace.
[0050] In some embodiments of the present invention, the carbonization treatment temperature is 300-450°C.
[0051] In some embodiments of the present invention, the carbonization treatment temperature is 300-400°C.
[0052] In some embodiments of the present invention, the carbonization treatment temperature is 350° C. Under low-temperature carbonization, wood powder, starch, and cuttlefish ink powder will release some gases (carbon dioxide produced by wood powder and starch; volatile organic compounds produced by wood powder and cuttlefish ink powder; residual water vapor in the material). These gases will make the composite material expanded by restricted foaming densely covered with various fine channels. The wood powder evenly distributed in the material forms micro-nano-scale channels due to the molecular volume being reduced after carbonization, which can construct a large number of capillary self-evaporation channels with interlaced pore paths, so that the efficient water absorption capacity further enhances the evaporation purification effect of the material after photothermal conversion.
[0053] In some embodiments of the present invention, the carbonization treatment time is 1-2.5 hours.
[0054] According to a second aspect of the present invention, a fully biomass porous photothermal composite material with enhanced surface microstructure is proposed, which is prepared by the above method.
[0055] The surface microstructure enhanced all-biomass porous photothermal composite material of the present invention effectively utilizes the surface microstructure with micro-nano size on the upper surface of the composite material to enhance light refraction and light absorption, and at the same time constructs a large number of continuous and interconnected micro-nano pore channels to provide water transmission and purification channels, and utilizes cuttlefish ink powder and carbonized wood powder to further improve the photothermal conversion capacity and evaporation effect of the composite material.
[0056] According to a third aspect of the present invention, an application of the above-mentioned all-biomass porous photothermal composite material with surface microstructure enhancement is proposed, and the application is application in seawater desalination.
[0057] In some embodiments of the present invention, the application is application in sewage treatment.
[0058] In some embodiments of the present invention, the application is application in oil-water separation.
[0059] According to some embodiments of the present invention, there are at least the following beneficial effects:
[0060] The present invention provides a method for preparing a full-biomass porous photothermal composite material with enhanced surface microstructure. The method directly utilizes raw materials from nature, constructs a multi-level pore structure and a large number of carbon particles through low-temperature restricted carbonization, and simultaneously utilizes the surface microstructure to enhance the light conversion effect, thereby manufacturing a high-performance photothermal full-biomass porous composite material with good water absorption, high photothermal conversion capacity, rapid evaporation purification capacity, and degradability in a green and low-cost manner.
[0061] This method has extremely wide material applicability and is suitable for agricultural and forestry resources such as bamboo, wood, straw and their waste. All raw materials are biomass materials derived from agricultural and forestry resources and marine organisms. It is expected to promote the high-value utilization of agricultural and forestry resources and the "transformation of waste into treasure" of agricultural and forestry waste resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0063] Figure 1 is a flow chart of the preparation method in Example 1 of the present invention;
[0064] Figure 2 This is the preparation and molding process of the all-biomass porous photothermal composite material in Example 1 of the present invention;
[0065] Figure 3 This is a microscopic image of the internal morphology of the carbonized precursor material in Example 1 of the present invention;
[0066] Figure 4 This is a microscopic morphology of the material after low-temperature carbonization and restricted expansion in the test example of the present invention;
[0067] Figure 5 This is a super-depth surface microstructure diagram of the all-biomass porous photothermal composite material with surface microstructure enhancement in the test example of the present invention;
[0068] Figure 6 This is a test result diagram of the hydrophilic and hydrophobic properties of the all-biomass porous photothermal composite material with surface microstructure enhancement in the test example of the present invention;
[0069] Figure 7 A schematic diagram of the surface microstructure of the all-biomass porous photothermal composite material with surface microstructure enhancement in the test example of the present invention and its absorption of sunlight;
[0070] Figure 8 Schematic diagram of sewage treatment by the all-biomass porous photothermal composite material with surface microstructure enhancement in the test example of the present invention, wherein 1 is the all-biomass porous photothermal composite material, 2 is water molecules, 3 is suspended particles, 4 is heavy metal ions, and 5 is macromolecules;
[0071] Fig. 9 This is a picture showing the effect of a field experiment of water evaporation in a test example of the present invention;
[0072] Fig.10 This is a comparison chart of the effects of methylene blue before and after purification in the test example of the present invention;
[0073] Fig.11 This is a comparison chart of the effects before and after methyl orange purification in the test example of the present invention. DETAILED DESCRIPTION
[0074] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0075] Example 1
[0076] This embodiment provides a surface microstructure enhanced all-biomass porous photothermal composite material, the preparation process is as follows Figure 1 As shown, the preparation process is as follows Figure 2 As shown, it is specifically prepared by the following preparation method:
[0077] (1) Weigh 30 g of pine wood powder (280 mesh), 24 g of starch, and 6 g of cuttlefish powder, dissolve them in 50 ml of deionized water, and premix them in a mixing machine to obtain a premix. The speed of the mixing machine is about 300 r / min, and the mixing time is 15 min.
[0078] (2) The premix is heated in a water bath at 90° C. for 15 min to obtain a gelatinized blend.
[0079] (3) The gelatinized blend was placed into a circular mold with a diameter of 8 cm and extruded to form the mixture.
[0080] (4) The shaped gelatinized blend is placed in a vacuum dryer for vacuum drying at a temperature of 80° C. for 2 h, until the gelatinized blend has a water content of 6 wt %, to obtain a dried mixture.
[0081] (5) The dried mixture was placed in a molding machine for molding, with a molding time of 10 min, a molding temperature of 180° C., and a molding pressure of 10 MPa to obtain a carbonized precursor (the carbonized precursor was characterized, and its microscopic morphology was as follows Figure 3 As shown, the wood powder strips are bonded together by starch, and the cuttlefish powder particles fill the gaps).
[0082] (6) The template with the surface microstructure (the papillary microstructure with the light trapping effect) is fixedly installed on the inner cavity surface of the closed mold (a non-overflow pressing mold, the inner cavity size of the mold is selected according to the size of the carbonized precursor, slightly larger than the sample size, and the top of the mold is a cavity with a surface microstructure), and the above-mentioned carbonized precursor is placed in the mold with the surface microstructure and sealed (after sealing, the air content in the closed mold is 5% to 10%), and then placed in a muffle furnace for low-temperature carbonization and expansion molding. The low-temperature carbonization treatment temperature is 350°C and the low-temperature carbonization treatment time is 2h. To obtain an all-biomass porous photothermal composite material with a continuous and interconnected micro-nanopore structure inside and a light trapping microstructure on the surface.
[0083] Example 2
[0084] This embodiment provides a biomass porous photothermal composite material with enhanced surface microstructure, which is prepared by the following preparation method:
[0085] (1) Weigh 24 g of pine wood powder (280 mesh), 30 g of starch, and 6 g of cuttlefish powder, dissolve them in 50 ml of deionized water, and premix them in a mixing machine to obtain a premix. The speed of the mixing machine is about 300 r / min, and the mixing time is 15 min.
[0086] (2) The premix is heated in a water bath at 90° C. for 15 min to obtain a gelatinized blend.
[0087] (3) The gelatinized blend was placed into a circular mold with a diameter of 8 cm and extruded to form the mixture.
[0088] (4) The shaped gelatinized blend is placed in a vacuum dryer for vacuum drying until the gelatinized blend has a water content of 6 wt % and a drying temperature of 80° C., thereby obtaining a dried mixture.
[0089] (5) The dried mixture was placed in a molding machine for molding at a molding time of 10 min, a molding temperature of 180° C., and a molding pressure of 10 MPa to obtain a carbonized precursor.
[0090] (6) The template with the surface microstructure (the papillary microstructure with the light trapping effect) is fixedly installed on the inner cavity surface of the closed mold (a non-overflow pressing mold, the inner cavity size of the mold is selected according to the size of the carbonized precursor, slightly larger than the sample size, and the top of the mold is a cavity with a surface microstructure), and the above-mentioned carbonized precursor is placed in the mold with the surface microstructure and sealed (after sealing, the air content in the closed mold is 5% to 10%), and then placed in a muffle furnace for low-temperature carbonization and expansion molding. The low-temperature carbonization treatment temperature is 350°C and the low-temperature carbonization treatment time is 2h. To obtain an all-biomass porous photothermal composite material with a continuous and interconnected micro-nanopore structure inside and a light trapping microstructure on the surface.
[0091] Test example
[0092] This test example characterized the surface microstructure enhanced all-biomass porous photothermal composite material prepared in Example 1, and tested the sewage purification effect.
[0093] 1. Characterization of all-biomass porous photothermal composite materials with enhanced surface microstructure
[0094] (1) Characterization of all-biomass porous photothermal composite materials with enhanced surface microstructure
[0095] Experimental method: The surface microstructure enhanced all-biomass porous photothermal composite material prepared in Example 1 was characterized by scanning electron microscopy (SEM).
[0096] The results are as follows Figure 4 As shown in the figure, it can be seen that the all-biomass porous photothermal composite material with surface microstructure enhancement prepared by the scheme of the present invention has a continuous and interconnected micro-nanopore structure inside and a light-trapping microstructure on the surface.
[0097] (2) Surface microstructure characterization
[0098] Experimental method: The surface microstructure of the all-biomass porous photothermal composite material with surface microstructure enhancement prepared in Example 1 was characterized using an ultra-depth-of-field microscope.
[0099] The results are as follows Figure 5 As shown in the figure, it can be seen that the surface of the all-biomass porous photothermal composite material prepared by the present invention has been evenly distributed with papillary microstructures with light trapping effect, which can enhance the light refraction and light absorption of the all-biomass porous photothermal composite material, and further improve the photothermal conversion efficiency.
[0100] (2) Hydrophilicity and hydrophobicity test
[0101] Experimental method: The contact angle experiment was used to test the hydrophilicity and hydrophobicity of the surface microstructure enhanced all-biomass porous photothermal composite material prepared in Example 1.
[0102] The results are as follows Figure 6 As shown in the figure, it can be seen that the all-biomass porous photothermal composite material with surface microstructure enhancement prepared by the scheme of the present invention is hydrophilic.
[0103] 2. Wastewater treatment test using solar interface evaporation purification
[0104] The surface microstructure-enhanced all-biomass porous photothermal composite material prepared by the present invention can purify sewage by solar interface evaporation. The schematic diagram of the surface microstructure absorbing sunlight is shown in FIG. Figure 7 As shown, the obtained all-biomass porous photothermal composite material is applied to sewage treatment. The sewage treatment principle is as follows Figure 8 As shown, the specific principle is: the all-biomass porous photothermal composite material 1 uses its own micro-nano pores to absorb, isolate and purify macromolecules such as organic waste 3, suspended particles 4, heavy metal ions 5 in domestic sewage, and quickly absorbs water molecules 2 and then uses solar energy interface evaporation to purify the sewage.
[0105] Experimental method: A water evaporation experiment was used for verification. Specifically, 15 g of the surface microstructure enhanced all-biomass porous photothermal composite material prepared in Example 1 was used for water evaporation test, the water volume was 100 mL, and the test time was 1 hour.
[0106] The experimental results are as follows Fig. 9 As shown, from Fig. 9 It can be seen that the water evaporation effect is obvious, and the evaporation amount is about 2kg / m 2 h.
[0107] 3. Treatment of organic dye wastewater
[0108] Experimental method: 15 g of the surface microstructure enhanced all-biomass porous photothermal composite material prepared in Example 1 was added to 100 mL of wastewater containing methylene blue and methyl orange (the concentrations of methylene blue and methyl orange in the wastewater were 50 mg / L, respectively), and the treatment time of the all-biomass porous photothermal composite material and the wastewater was 1 hour.
[0109] The results are as follows Figure 10-11 As shown in the figure, it can be seen that the all-biomass porous photothermal composite material with surface microstructure enhancement prepared by the scheme of the present invention can be effectively used for organic dye wastewater treatment, and the purification rate can reach 96%.
[0110] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing a porous biomass photothermal composite material with enhanced surface microstructure, characterized in that: The preparation method comprises the following steps: S1, mixing wood powder, bio-based polymer material and biomelanin to obtain a mixture; S2, heating the mixture to obtain a gelatinized blend; S3, drying the gelatinized blend, and then performing a molding process at 100° C.-190° C. to obtain a carbonized precursor; S4, placing the carbonized precursor in a mold and sealing it, and performing a carbonization treatment to obtain the all-biomass porous photothermal composite material.
2. The preparation method according to claim 1, characterized in that: The wood powder includes but is not limited to one of straw, pine wood and bamboo.
3. The preparation method according to claim 1, characterized in that: The bio-based polymer material includes but is not limited to one of starch and cellulose.
4. The preparation method according to claim 1, characterized in that: The biomelanin includes at least one of cuttlefish ink and squid ink.
5. The preparation method according to claim 1, characterized in that: The added mass ratio of the wood powder, bio-based polymer material and bio-melanin is (3-6): (3-6):
1.
6. The preparation method according to claim 1, characterized in that: The heating temperature is 60-95° C. and the heating time is 10-25 min.
7. The preparation method according to claim 1, characterized in that: The molding time is 5-15 minutes, and the pressure is 5-15 MPa.
8. The preparation method according to claim 1, characterized in that: The carbonization treatment temperature is 300-450°C; And / or, the carbonization treatment time is 1-2.5h.
9. A biomass porous photothermal composite material with enhanced surface microstructure, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the all-biomass porous photothermal composite material with surface microstructure enhancement according to claim 9 in any of the following: (1) Seawater desalination; (2) Wastewater treatment; (3) Oil-water separation.